2020
DOI: 10.31487/j.jicoa.2020.02.05
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Postpartum Counseling on Future Health Risks Associated with Hypertensive Disorders of Pregnancy

Abstract: Background: The American College of Obstetricians and Gynecologists and the American Heart Association recommend that women with hypertensive disorders of pregnancy be counseled on lifelong cardiovascular risks and transitioned to primary care for ongoing screening and management. Objective: To assess frequency and content of postpartum counseling regarding cardiovascular risk and follow-up among women with hypertensive disorders of pregnancy. Study Design: A secondary analysis of a randomized trial of women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…12 Among women with HDP excluding all women with chronic hypertension, less than 10% of women were counseled on transitions of care, CVD risk, and aspirin in future pregnancies. 13 We found that the only patient-level characteristic associated with documented counseling was black race. There are some data that non-white women are less likely to perceive CVD as a significant personal health risk, although the gap in awareness has decreased over time.…”
Section: Original Researchmentioning
confidence: 78%
See 1 more Smart Citation
“…12 Among women with HDP excluding all women with chronic hypertension, less than 10% of women were counseled on transitions of care, CVD risk, and aspirin in future pregnancies. 13 We found that the only patient-level characteristic associated with documented counseling was black race. There are some data that non-white women are less likely to perceive CVD as a significant personal health risk, although the gap in awareness has decreased over time.…”
Section: Original Researchmentioning
confidence: 78%
“…10,11 Although the postpartum period is a critical time to promote women's cardiovascular health, limited data suggest that counseling is not routine. 12,13 We hypothesized that most women with HDP do not receive adequate counseling about the long-term sequelae of these disorders in the postpartum period. We measured the documentation of counseling on factors that would have a direct impact on future maternal health including future risks of CVD, transition to continuity providers including primary care providers (PCPs) and cardiologists, and recommendation for aspirin use in subsequent pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…20 In prior studies using medical record review for patients with hypertensive disorders of pregnancy, few had documented counseling on transitions of care to primary care or based on CVD risk. 15,21 Current recommendations for care after hypertensive disorders of pregnancy are limited in scope or detail, 6,7 focus on hospital discharge as the time to provide counseling, 16 and do not address how to successfully transition patients to preventive care clinicians. Uncertainty about how to counsel and screen for CVD risk may affect the implementation of postpartum counseling on hypertensive disorders of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…20 In prior studies using medical record review for patients with hypertensive disorders of pregnancy, few had documented counseling on transitions of care to primary care or based on CVD risk. 15,21…”
Section: Discussionmentioning
confidence: 99%